Medium raw a bloody valentine to the world of food and the people who cook - Bourdain, Anthony (Ecco Press, 2010)
Tracking his own strange and unexpected voyage from journeyman cook to globe-traveling professional eater and drinker, and even to fatherhood, Bourdain takes no prisoners as he dissects what he's seen, pausing along the way for a series of confessions, rants, investigations, and interrogations of some of the most controversial figures in food.